Peran P2P Lending dan Digitalisasi terhadap Tingkat Kemiskinan di Indonesia - Chang, Nicholas; Octavia, Louisa (Accounting Study Program, Universitas Ciputra Surabaya, 2026)
Poverty in Indonesia still shows disparities between provinces amid the acceleration of digital transformation. From an inclusive growth perspective, equitable access to productive resources, including the digital economy, is an important prerequisite for sustainable poverty reduction. This study aims to analyze the effect of peer-to-peer (P2P) lending, digital skills, and digital infrastructure on poverty levels across provinces in Indonesia. The study uses a quantitative approach with a multiple linear regression method based on cross-section data from 38 provinces sourced from the Financial Services Authority and the Central Statistics Agency. The results show that simultaneously, all three digital economy variables have a significant effect on poverty. However, partially, only digital infrastructure has a negative and significant effect on poverty levels, while P2P lending and digital skills do not show a significant effect. These findings indicate that the equitable distribution and quality of digital infrastructure are the main foundations in supporting poverty reduction based on digital transformation. This study concludes that the digital economy can be an instrument of inclusive development if it is supported by strengthening structural access between regions. Policy implications emphasize the importance of prioritizing digital infrastructure development as a prerequisite for effective financing and improving digital skills.